2008
DOI: 10.1159/000187169
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of Serum Procalcitonin Levels following Direct Hemoperfusion with Polymyxin B-Immobilized Fiber Column in Septic Patients with Colorectal Perforation

Abstract: Background: The efficacy of direct hemoperfusion with polymyxin B-immobilized fiber columns (PMX) has already been demonstrated in clinical studies for the treatment of septic shock. However, serum procalcitonin levels following PMX remain unknown. Methods: This prospective, multicenter, nonrandomized clinical study was performed at 12 institutions. Forty-five patients with severe sepsis or septic shock due to colorectal perforation underwent PMX. Patients’ outcome as well as circulating levels of endotoxin, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…When this inflammation spreads to the brain parenchyma and cerebral blood vessels, it causes cerebral edema, increased intracranial pressure, cerebrovascular disability, cerebral vasculitis, and neuronal damage, which leads to poor outcomes such as neurological sequelae and death . PMX‐DHP may suppress inflammation by absorbing activated leukocytes and LTA and reducing pro‐inflammatory cytokines . Eight of our 10 patients were identified to have Gram‐positive bacteria, which do not have lipopolysaccharide.…”
Section: Discussionmentioning
confidence: 99%
“…When this inflammation spreads to the brain parenchyma and cerebral blood vessels, it causes cerebral edema, increased intracranial pressure, cerebrovascular disability, cerebral vasculitis, and neuronal damage, which leads to poor outcomes such as neurological sequelae and death . PMX‐DHP may suppress inflammation by absorbing activated leukocytes and LTA and reducing pro‐inflammatory cytokines . Eight of our 10 patients were identified to have Gram‐positive bacteria, which do not have lipopolysaccharide.…”
Section: Discussionmentioning
confidence: 99%
“…Timing of blood sampling is basically in the day before surgery or before induction of anesthesia. PCT was measured by Elecsys® Brahms PCT and Cobas 8000® (Roche Diagnostics Corporation, Tokyo, Japan; range 0.05–100 ng/mL) [11]. The mGPS and PNI were evaluated as previously described [5, 6].…”
Section: Methodsmentioning
confidence: 99%
“…First, fulminant CDAC with MODS is caused by the shift from an inflammatory response at a local mucosal level to a general systemic inflammatory reaction in which CD toxin-induced mediators’ cascades disseminate [ 30 36 ]. Second, although PMX-HP removes circulating endotoxin by adsorption and theoretically prevents the progression of the biological cascade of sepsis, several studies and published reports have demonstrated that PMX-HP can reduce the plasma levels of cytokines and sepsis-related factors, namely TNF-α, IL-6, IL-10, N -arachidonoylethanolamine (AEA), 2-arachidonoyl glycerol (2-AG), and high-mobility group box-1 (HMGB-1) [ 21 , 23 , 38 , 39 ]. Indeed, there were case reports published which showed that PMX-HP decreases the serum levels of endogenous cannabinoids (anandamide and 2-AG) and inflammatory cytokine (IL-6) in parallel with the clinical improvement of fulminant CDAC [ 40 , 41 ].…”
Section: Case Presentationmentioning
confidence: 99%